Hardware-in-the-loop pantograph tests using analytical catenary models. Issue 10 (3rd October 2022) - Gil, J.; Tur, M.; Correcher, A.; Gregori, S.; Pedrosa, A.; Fuenmayor, F. J.
Abstract : Pantograph hardware-in-the-loop (HIL) testing is an experimental method in which a physical pantograph is excited by an actuator which reproduces the movement of a virtual catenary. This paper proposes a new method that uses analytical catenary models for HIL tests. The approach is based on an iterative scheme until achieving a steady-state regime. Some of the method's advantages include its ability to consider the delay in the control and communication system and its applicability to a wide range of analytical catenary models. The proposed algorithm was validated both numerically and experimentally. The experimental results obtained in the HIL pantograph tests were compared with those obtained from pure numerical simulations using a linear pantograph model and showed good accuracy with pantograph running at different speeds.